2005
DOI: 10.1002/path.1822
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of c‐kit and stem cell factor in primary and metastatic nasopharyngeal carcinomas and nasopharyngeal epithelium

Abstract: Expression of c-kit has been demonstrated in 33% of adult nasopharyngeal carcinomas (NPCs) and in 88% of paediatric NPCs. Patients with tumours expressing c-kit tend to exhibit better survival, but a paracrine/autocrine function for the stem cell factor (SCF)/c-kit system in nasopharyngeal carcinomas has not been reported. This study evaluated the expression of c-kit and SCF by immunohistochemical staining of nasopharyngeal epithelium (NPE) and of primary and metastatic NPCs. In addition, c-kit and SCF express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…In studies that involve metastatic nasopharyngeal carcinoma it was found that activation of SCF/c-Kit signaling potentially contributes to carcinogenesis and progression of this cancer. 37 Finally, in human uveal melanoma the SCF/c-Kit axis was found to play a role in increasing melanoma transformation and proliferation, 37,38 supporting our present studies that this axis may also be important in CCA proliferation.…”
Section: Discussionsupporting
confidence: 73%
“…In studies that involve metastatic nasopharyngeal carcinoma it was found that activation of SCF/c-Kit signaling potentially contributes to carcinogenesis and progression of this cancer. 37 Finally, in human uveal melanoma the SCF/c-Kit axis was found to play a role in increasing melanoma transformation and proliferation, 37,38 supporting our present studies that this axis may also be important in CCA proliferation.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, we need to use a much higher concentration of ApoG2 to kill HONE-1 cells. Also, there may be plenty of other prosurvival molecules, such as c-kit/SCF, 54 that prevent HONE-1 cells from undergoing apoptosis.…”
mentioning
confidence: 99%
“…The EBNA1 gene was introduced into the pCP4/EBNA1 plasmid and the control pCP4 vector, and the DNA transfection methods are as previously described (44). The pCP4/EBNA1 plasmid was used to transfect SCM1, TMC1 and LL/2 cells to establish the EBNA1-expressing cells to evaluate the biological effects of EBNA1 in transfected cells.…”
Section: Cells and Animalsmentioning
confidence: 99%
“…Western immunoblotting was used to evaluate EBNA1 expression in tumor masses derived from the tumorigenic assay in nude mice or Balb/c mice as described in a previous report with minor modifications (36,44). In brief, the extracted protein concentration was determined by a bicinchonic acid assay (Pierce, Rockford, IL, USA), and an appropriate amount of protein was used for immunoprecipitation.…”
Section: Immunoprecipitation Of Ebna1 Immunoprecipitation Plusmentioning
confidence: 99%
See 1 more Smart Citation